Antagonism of cadmium-induced liver injury in ducks by α-bisabolol - Elazab, Sara T.; Hsu, Walter H. (Frontiers in Veterinary Science, 2022)
Cadmium (Cd) is an ecological pollutant which causes hazardous effects in animals and humans. The aim of this study was to investigate the role of α-bisabolol (BISA) in antagonizing the Cd-induced hepatotoxicity in ducks. Two-week old ducks were allocated into 8 groups (10 ducks/group): Group I received basal diet and was gavaged with sunflower oil (BISA vehicle, 1.1 mL/kg/day); group II was administered BISA orally (50 mg/kg/day; diluted with sunflower oil); groups III, IV, and V were fed the basal diet mixed with CdCl2 at 37.5, 75, and 150 mg/kg diet, respectively, and were gavaged with sunflower oil; group VI, VII, and VIII were given basal diet containing CdCl2 at the aforementioned consecutive doses plus BISA. All treatments were provided daily for 4 weeks. Exposure to CdCl2 induced mortality in ducks, increased hepatic Cd content and serum levels of hepatopathic biomarkers, and caused oxidative stress and morphological alterations in ducks' liver. Furthermore, exposure to Cd caused upregulation of the mRNA of proinflammatory cytokine tumor necrosis factor-α and apoptotic gene Bax, and that of cyclooxygenase-2 protein in the liver. All effects of Cd were dose-dependent. BISA antagonized all of the aforementioned CdCl2-induced changes. These findings suggested that BISA exert the hepatoprotective effect against Cd toxicity through reducing the hepatic content of Cd as well as antagonizing oxidative insults, inflammation, and apoptosis. Thus, BISA has a great potential to be used as an antidote in the control of Cd poisoning.